The role of snorc, a novel cartilage transmembrane proteoglycan in skeletal tissue homeostasis - Heinonen, Jussi (fi=Turun yliopisto|en=University of Turku|, 2017)
Discovery of molecular mechanisms underlying chondrogenesis is necessary to develop therapies for skeletal disorders and articular cartilage defects or disorders like osteoarthritis (OA). Specific properties of each tissue are derived from tissue-specific gene expression. Therefore, it is likely that genes with tissue-specific expression have an important role in development of structural and functional properties of tissue. Remarkable number of genes associated with OA and genetic skeletal disorders have a cartilage-selective expression pattern. Some of these are proteoglycans (PG), which are important structural components of cartilage extracellular matrix (ECM) and modulators of activity of extracellular signal molecules. The aim of the study was to discover novel genes essential in chondrogenesis and cartilage homeostasis by transcriptional profiling. Of the large-scale analysis, a promising transcript named Snorc (small novel rich in cartilage), was selected for more specific analysis. The aim of the analysis was to define expression and structure of Snorc gene and protein, to define interaction partners of Snorc protein and to analyze the role of the Snorc gene in mouse skeletal tissue development. Snorc is a type I single-pass transmembrane chondroitin or dermatan sulfate PG, highly conserved in vertebrates. Expression of Snorc was observed throughout life span in mouse epiphysis especially during development. Expression is most intense in proliferative and prehypertrophic cartilage of growth plate (GP) during embryonic development, and in prehypertrophic chondrocytes surrounding secondary ossification center (SOC) during postnatal development. Messenger RNA is cartilage-specific, but immunoreactivity was detected also in ECM of trabecular bone. Size of mineralized SOC is decreased and structure of GP disturbed in Snorc-deficient mice knee epiphysis, compared to wild type (WT). Proliferative and hypertrophic zones were enlarged, especially in medial part, and chondrocyte morphology was changed in Snorc-deficient mice GP at postnatal day (P) 10 and 22. Indian hedgehog (Ihh) and collagen type X alpha 1 chain (Col10a1) expression were increased and matrix metalloproteinase 13 (Mmp13) decreased in P10 Snorc-deficient mouse epiphysis. Peripheral quantitative tomography revealed increase in endosteal and in periosteal perimeter, and in the area of trabecular bone in the cross-section of distal femoral metaphysis in adult Snorc-deficient mice compared to WT. However, alterations in long bone length were not observed. Bone morphogenetic protein 2 induced expression of Snorc in chondrocytes. Snorc extracellular domain (ECD) binds fibroblastic growth factor 2 (Fgf2) independently of glycosaminoglycan chain of Snorc. Snorc is a novel cartilage-specific transmembrane PG with a role in maturation of postnatal GP chondrocytes, epiphyseal ossification and metaphyseal bone formation in mouse. Snorc-deficiency caused alterations in expression of Ihh and Mmp13 genes in postnatal epiphysis. Ihh is important regulator of proliferative zone and Mmp13 necessary for vascularization and ossification of cartilage. Binding of Fgf2 to Snorc ECD clues that Snorc may have a role in Fgf signaling potentially as a coreceptor.

Ruston kehityksessä tärkeiden molekyylibiologisten mekanismien tunteminen on välttämätöntä, jotta on mahdollista kehittää hoitoja esim. tukirangan kehityshäiriöihin ja nivelruston vaurioihin ja sairauksiin kuten nivelrikkoon. Kullekin kudokselle ominaiset geenien ilmenemisprofiilit määrittävät kudoksen ominaisuudet, joten on todennäköistä, että kudosspesifisesti ilmenevällä geenillä on erityinen rooli kudoksen rakenteellisten ja toiminnallisten ominaisuuksien kehittymisessä. Merkittävällä määrällä nivelrikkoon ja tukirangan kehityshäiriöihin liitetyistä geeneistä ilmeneminen on rustolle ominainen. Näistä osa koodaa proteoglykaaneja, jotka ovat tärkeitä ruston soluväliaineen rakenteellisia komponentteja ja solunulkoisten signaalimolekyylien toiminnan säätelijöitä. Tämän työn tavoitteena oli löytää uusia, ruston kehityksessä ja homeostaasissa oleellisia geenejä seulomalla uusia, aiemmin tunnistamattomia RNA-transkripteja, jotka ilmenevät spesifisesti rustossa kehityksen aikana. Lupaava RNA-transkripti, Snorc (small novel rich in cartilage), valittiin tarkempaa tutkimusta varten, jonka tavoitteena oli selvittää geenin ja proteiinin ilmenemistä ja rakennetta, proteiinin vuorovaikutuskumppaneita ja geenin roolia hiiren tukirangan kehityksessä. Snorc on tyypin I integraalinen kondroitiini- tai dermataanisulfaattikalvoproteoglykaani, joka on säilynyt hyvin selkärankaisten evoluutiossa. Snorc ilmenee hiiren epifyysirustossa läpi elämän, mutta erityisesti kehityksen aikana. Sikiökehityksen aikana ilmeneminen on voimakkainta kasvulevyn proliferatiivisessa ja prehypertrofisessa rustossa ja syntymän jälkeisen kehityksen aikana sekundaarisen luutumiskeskuksen (SOC) ympärillä. Lähetti-RNA ilmenee spesifisesti rustossa, mutta proteiinia nähdään myös hohkaluun soluväliaineessa. Snorc-poistogeenisen (KO) hiiren polven epifyysissä SOC oli pienentynyt ja kasvulevyn rakenne häiriintynyt verrattuna villityypin hiireen. Kasvulevyn proliferatiivinen ja hypertrofinen vyöhyke olivat laajentuneet erityisesti keskiosastaan ja rustosolujen muoto oli muuttunut Snorc KO hiiressä 10. ja 22. päivä syntymän jälkeen. Indian hedgehog (Ihh), ja tyypin 10 kollageeni alfa 1 ketju (Col10a1) -geenien ilmeneminen oli lisääntynyt ja matriksin metalloproteinaasi 13 (Mmp13) vähentynyt Snorc KO-hiiren epifyysissä 10. päivä syntymän jälkeen. Perifeerinen kvantitatiivinen tomografia osoitti endosteaalisen ja periosteaalisen kehän ja hohkaluun pinta-alan kasvamisen reisiluun ulomman metafyysin poikkileikkauksessa aikuisella Snorc KO-hiirellä. Luun morfogeneettinen proteiini 2 sai aikaan Snorcin ilmenemistä. Fibroblastinen kasvutekijä 2 (Fgf2) sitoutui Snorcin solunulkoiseen rakennealueeseen glykosaminoglykaanista riippumatta. Tutkimukset osoittivat, että Snorc on uusi rustospesifinen solukalvon läpäisevä proteoglykaani, jolla on rooli syntymänjälkeisen kasvulevyn kehityksessä, epifyysin luutumisessa ja metafyseaalisen luun muodostumisessa hiiressä in vivo. Snorcin toiminnan esto aiheutti muutoksia Ihh ja Mmp13 geenien ilmenemisessä syntymänjälkeisessä epifyysissä. Ihh on tärkeä proliferatiivisen vyöhykkeen säätelijä ja Mmp13 välttämätön ruston verisuonten muodostumisessa ja luutumisessa. Fgf2 sitoutuu Snorcin solunulkoiseen osaan, mikä viittaa siihen, että Snorcilla olisi rooli Fgf signaloinnissa mahdollisesti koreseptorina